The Right to Play: Interpretation through the Lens of the Convention on the Rights of the Child - Garayová, Lilla (European Integration Studies, 2023)
Children’s rights are human rights. When internalizing this mantra, it is crucial to understand that children are not only the youngest and most vulnerable population group but also that they have their own particular needs. To ensure that these needs are met, we must recognize an additional subset of human rights that are unique to children. These are comprehensively represented in the United Nations Convention on the Rights of the Child, including, among others, the right to protection from all forms of violence, the right to play, and children’s right to express their views in matters affecting them. Children’s rights, however, require more than just an understanding of the relevant theory and implementation of these rights is lagging dangerously behind what is optimal. This shortcoming is further amplified in cases involving certain so-called forgotten rights, and even among these, the right to play is undoubtedly the red-headed stepchild of the Convention that is often overlooked and constantly undervalued.